Muslim American physicians’ views on brain death: Findings from a national survey - Popal, Sadaf; Hall, Stephen; Padela, Aasim I (Avicenna Journal of Medicine, 2021)
Background: Biotechnology has introduced a new physiological state, “brain death,” that continues to attract controversy and confusion. While variability in diagnostic criteria for, and physician practices regarding, “brain death” has been studied, few studies examine physicians’ normative views on the significance of “brain death” and how religiosity implicates these views. Objective: The objective is to assess how Muslim physicians’ views on death, and how their religiosity and acculturation, associate with their perceptions of “brain death.” Methods: A randomized national sample of 626 American Muslim physicians completed a mailed questionnaire assessing sociodemographic characteristics, religiosity, and views about death. Measures of religious practice and acculturation were analyzed as predictors of physician views at the bivariate and multivariable levels. In conducting the multivariate analysis, P-values less than 0.05 were deemed statistically significant. Results: Two-hundred and fifty-five respondents completed the survey (41% response rate). Most participants agreed that death is the irreversible cessation of cardiac and respiratory function (90%), while half agreed or disagreed with other definitions of death, such as loss of personhood or the equivalence of cardiopulmonary and neurological criteria for death. Physicians who scored higher on the religious practice scale had significantly lower odds of agreeing with the statement; “brain death” signifies the departure of the soul from the body [odds ratio (OR) = 0.57, 95% confidence interval (CI): 0.33–0.98]. Those who were born in the US, or immigrated to the US as a child, had greater odds of viewing death as the irreversible loss of personhood and consciousness [OR = 3.52, 95% CI: 1.62–7.63]. Conclusion: Physician characteristics such as religiosity and acculturation appear to influence their views on what constitutes death and how it should be diagnosed. In our sample of Muslim physicians, there appears to be significant reservation toward equating neurological and cardiopulmonary criteria to determine death and disquiet regarding the meaning of “brain death” in general.
Keywords: Doctors; end-of-life; ethics; Islam; personhood